Bibliometric analysis of focal therapy in prostate cancer research - Mohammed Shahait; Sarah Ibrahim; Laith Baqain; Zahi Abdul‐Sater (BJUI Compass)
Abstract Introduction The use of focal therapies for prostate cancer (PCa) has soared, as it controls disease and is associated with minimal side effects. Bibliometric analysis examines the global research landscape on any topic to identify gaps in the research and areas for improvement and prioritize future research efforts. This study aims to examine the research outputs and trends and collaboration landscape in the field of focal therapy for PCa on a global scale. Methods We searched Medline, PubMed and Scopus for peer‐reviewed publications on our research topic using controlled keywords. Search results were limited to the period between 1980 and 2022, screened for duplicates and then included in our study based on prespecified eligibility criteria. The Bibliometrix Package was used for comprehensive science mapping analysis of co‐authorship, co‐citation and co‐occurrence analysis of countries, institutions, authors, references and keywords in this field. Results This analysis included 2578 research articles. The annual scientific production increased from one article in 1982 to 143 in 2022 (13.21%). The average citation per year was incrementally increasing, and these documents were cited around 32.52 times. The documents included in this analysis were published in 633 sources. The international collaboration index was 22.7. In total, 6280 author keywords were identified. The most used keywords were ‘prostate cancer’, ‘focal therapy’, ‘prostate’ and ‘photodynamic therapy’. Conclusion This bibliometric analysis has provided a comprehensive review of focal therapy in PCa research, highlighting both the significant growth in the field and the existing gaps that require further exploration. The study points to the need for more diverse international collaboration and exploration of various treatment modalities within the context of focal therapy.